RESPON TANAMAN JAGUNG MANIS PADA TANAH GAMBUT TERHADAP PEMBERIAN BEBERAPA JENIS BAHAN PEMBENAH TANAH - JUMADI, JUMADI; MUSTAMIR, ELLY; NURJANI, NURJANI (Jurnal Sains Mahasiswa Pertanian, 2018)
RESPON TANAMAN JAGUNG MANIS PADA TANAH GAMBUT TERHADAP PEMBERIAN BEBERAPA JENIS BAHAN PEMBENAH TANAH Jumadi(1), Elly Mustamir (2), Nurjani(3)(1)Mahasiswa Fakultas Pertanian dan (2) Staf Pengajar Fakultas Pertanian Universitas Tanjungpura Pontianak(3) Staf Pengajar Fakultas Pertanian Universitas Tanjungpura Pontianake-mail: jumadi_agrotek@yahoo.co.id ABSTRACTThe purpose of this research was to investigate the effect of five kind of soil enhancers to growth and yield of sweet corn plant grown on peat soil. This research was conducted on peat land located in Permata City Complex, Bansir Darat Village, Pontianak Southeast Subdistrict, Pontianak Regency, West Kalimantan Province. The study was conducted in December 2017 until February 2018 This research used field experiment with Randomized Block Design (RBD), with one factor, consit of 5 treatments and 5 replications, each treatment plot taken 4 plant samples. The treatment were: p1 = 2.5 kg of Dolomite Lime per block, p2 = 2.85 kg of Clam Powder per block, p3 = 4.56 kg burn of Ash Wood per block, p4 = 5,8 kg ash coconut husk per block, P5 = 7.12 kg of Palm Long Ash per block. Observational Variables observed were leaf area (cm2), root volume (cm3), dry weight (g), unsweethed cob weight per plant (g), cob length (cm), cob diameter (cm) and cob weight per block (kg) and the enviromental variables are Air Temperature (oC), Air Humidity (%), Rainfall (mm), and soil pH. Result of this research have significantly have to all observation variables. Based on the results of the study can be concluded that the provision of several types of soil enhancers apllied affect the growth and yield of sweet corn plants on peat soil. The burn of wood ash has a better effect when compared with other treatments on growth observations and sweet corn yields on peat soils.Keywords: Peat, ameliorant, and Sweet Corn.